Traditional Gymnastics For Elderly Health With Hypertension - Yasin, Dudella Desnani Firman; Widyastuti, Eny Erlinda; Hadi, Sopian (Universitas Tribhuwana Tunggadewi, 2025)
Aging is a natural process that every human undergoes, marking the final phase of life. Common issues among the elderly include declining sleep quality and fluctuations in blood pressure, which can significantly impact overall health. Research has shown that exercise combining movement with easily listenable music can positively affect blood pressure, improve sleep quality, and enhance balance in older adults. This study aims to analyze differences in blood pressure, sleep quality, and balance in the elderly following an exercise intervention. An institutional-based intervention design was used, providing integrative traditional exercise therapy to elderly groups in Pangkalpinang City. A total of 50 elderly participants were selected based on predetermined criteria and divided into two groups: an experimental group and a control group. The experimental group participated in an 8-week traditional exercise program called Senam Bedincak, a local exercise from Bangka Island, while the control group continued their usual activities. Post-intervention assessments measured sleep quality, blood pressure, and balance using questionnaires and observation sheets. Data analysis using the Wilcoxon test showed that the independent t-test for sleep quality resulted in a p-value of 0.000 (p 0.05), indicating a significant difference before and after the intervention in the experimental group.